ANALYSIS OF GAUSSIAN PLUME MODEL IN MICROSOFT EXCEL, MATLAB AND AERMOD IN AIR DISPERSION MODELLING - Fitri Milenia, Desmonda
Air pollution is a state when air contains unwanted substances in large enough quantities to have harmful effects on human health and the environment. In the era of globalization, increased productivity through the use of high-tech methods in industry and economic growth are the main causes of air pollution. EPA plays an important role in environmental governance and policy development around the world. One of the actions taken by EPA in preventing air pollution is air quality modelling. One of the programs used by the EPA in conducting air quality modelling is AERMOD. AERMOD can perform modelling for various source types, such as multiple point sources, line sources, and area sources. AERMOD uses a Gaussian Plume Model-type dispersion model that predicts the physical movement (such as plume rise and spread) of the plume in the surrounding area by considering complex topography, local weather and source characteristics. For comparison, the Gaussian Plume Model will be processed with MATLAB or MATrix Laboratory and Microsoft EXCEL. Of the three programs, AERMOD is superior in general air modelling and MATLAB is superior in simple Gaussian modelling than Microsoft EXCEL.